INTEGRASI LITERASI DIGITAL GURU DAN KURIKULUM BERBASIS CINTA DALAM IMPLEMENTASI SISTEM INFORMASI MANAJEMEN DI MADRASAH - Abam, Indra Mukti; Zainuri, Ahmad; Afriantoni, Afriantoni (Journal of Innovative and Creativity, 2026)
The study aims to analyze the integration of teachers’ digital literacy and a love-based curriculum in supporting the implementation of Management Information Systems (MIS) in madrasahs. Digital transformation in education encourages educational institutions to optimize the use of information technology in managing educational data and learning processes. However, the successful implementation of management information systems is not only determined by technological infrastructure but also by the competence of human resources and the value-based educational approach implemented within the institution. Materials and methods. This research employed a qualitative approach using a descriptive method. Data were collected through observation, in-depth interviews, and documentation. The research participants consisted of madrasah principals, teachers, and administrative staff who were directly involved in the management of educational information systems. The collected data were analyzed through data reduction, data presentation, and conclusion drawing to obtain a comprehensive understanding of the research phenomenon. Results. The findings indicate that teachers’ digital literacy plays a significant role in improving the effectiveness of management information system implementation, particularly in managing academic data, learning administration, and digital-based educational communication. In addition, the implementation of a love-based curriculum contributes to creating a more humanistic and collaborative learning environment that supports the integration of technology in madrasah education. Conclusions. The study concludes that the successful implementation of management information systems is influenced by the synergy between teachers’ digital competence, institutional support, and the educational values integrated into the curriculum. Strengthening teachers’ digital literacy and developing value-based curricula are therefore important strategies to support the optimization of technology-based educational management in madrasahs.